Determination of children and teenagers economical socialization: experimental research - A L Zhuravlev; T V Drobysheva (Peoples' Friendship University of Russia (RUDN University), 2009)
In the article results of natural forming social-psychological experiment are analyzed; dynamics of valuable orientations of the person of younger schoolboys reveal in conditions of early economic education and as psychological criterion of economic socialization.